Effect of adding Manganese sulfate for Diet on the hormonal and Histological response of aged Roosters exposed to Heat stress - Salman K.A.A; Mohammed Khalil Ibrahim Al-Saeedi; Hashim Hadi Al-Jebory (Kufa Journal for Agricultural Sciences)
This study was conducted in poultry farm of the college of Agriculture - Al-Qasim Green University, the effect of adding manganese sulfate for diet on the hormonal and histological response of aged roosters exposed to heat stress, 30 of Hy-Line roosters 50 week old was used, roosters were arbitrarily divided into 5 treatments,: 1st treatment T1: without manganese sulfates (comparison group), other treatments T2, T3, T4 and T5 were added manganese sulfates at (10, 20, 30, 40 mg / kg) respectively,  the experiment continued for six periods, each period lasting two weeks, the roosters were exposed to a temperature of 30 ⁰C during the experiment period, results of this experiment showed there was a significant improvement (P≤0.05)  for T3 and T5 in testosterone levels, and noticed significant increase of FSH in T4 and T5. There was a significant difference (P≤0.05) for T2 and T3 in GPX enzyme. In the thickness of the interstitial tissue, a significant difference (P≤0.05) was found in T3, a significant decrease (P≤0.05) was observed in the thickness of the germinal epithelium in T2 and T3, a significant difference (P≤0.05) in T3 noticed for diameter of the seminiferous tubes, a significant in the number of Sertoli cells for T3, and found a significant in the number of spermatozoa for treatments T2, T4 and T5. For the Vanguard of sperm, a significant increase in treatments T4 and T5. Significant increase of sperms was obtained in T2, T4 and T5 compared to T1.